OPINI PUBLIK SEBAGAI FAKTOR PEMBENTUK DISKRESI APARAT DALAM PENEGAKAN HUKUM: ANALISIS SOSIOLOGI HUKUM - Wisnu Sri Nurwening (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This study analyzes the role of public opinion in shaping the exercise of discretion by law enforcement officers in Indonesia. From a sociological law perspective, law is understood as a social institution that interacts with society, where public opinion can influence the legitimacy and practice of law enforcement. The phenomenon of penal populismindicates that public pressure often drives officers to make symbolic legal decisions, potentially blurring the normative boundaries of discretion. The study employs a qualitative descriptive approach, and analyzing legal documents and media reports. Thematic analysis is applied to explore the interaction between public opinion, penal populism, and officers’ discretion. Findings reveal that public opinion significantly affects the use of discretion, both directly and through the dynamics of penal populism. Discretion exercised professionally and based on legal principles enhances public trust, while distortion due to social pressure creates disparities and perceptions of injustice. This article emphasizes the importance of balancing responsiveness to public opinion with adherence to legal principles, as well as the need for accountability mechanisms and ethical training for law enforcement officers. The findings contribute to the development of sociological law studies and contemporary law enforcement practices.